Trance and the Semiotic Body: An Analysis of Gnaoua Possession Rituals in Morocco - Lahcen OUKHOUYA ALI (International Journal of Scientific Research and Innovative Studies, 2025)
In this article, we propose a semiotic analysis of Gnaoua possession rituals in Morocco, placing the body in a trance state at the centre of the analysis. Drawing on the theoretical framework of Peircean semiotics, Marcel Mauss’s contributions on bodily techniques, Gilbert Rouget’s phenomenology of ritual music, and the anthropological work of Ioan M. Lewis, we seek to demonstrate that the body of the possessed: the maalem or the initiate in trance, constitutes a complex semiotic text, articulating iconic, indexical and symbolic signs. Gestures, colours, musical rhythms and ritual scents form a coherent and coded system of meaning, the deciphering of which provides access to the deep grammar of the lila ritual. Drawing on ethnographic observations, we demonstrate how the body in trance becomes a mediating semiotic operator between the visible world and the invisible world of the spirits (mluk). This approach contributes to renewing studies on possession rituals in North Africa by integrating the conceptual tools of contemporary semiotics. Keywords: Gnaoua; trance; semiotic body; possession ritual; lila; semiotics; Morocco; mluk. Received Date: 20 October 2025 Accepted Date: 11 November 2025 Published Date: 1 December 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/715